2005
DOI: 10.1520/jai12371
|View full text |Cite
|
Sign up to set email alerts
|

Development of Fuel Clad Materials for High Burn-up Operation of LWR

Abstract: Oxide dispersion strengthening (ODS) steels have been considered to be very promising for fuel clad materials for high burn-up operation of light water reactor and super critical water reactor. For improving the corrosion resistance, increasing chromium concentration, which often resulted in degradation of mechanical properties and thermal embrittlement, has been required. In this work, the effects of aluminum addition on the mechanical properties of high chromium ODS steels have been investigated. Various ODS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…It is well known that the corrosion resistance in high-temperature water diminishes significantly with decreasing chromium concentration below 13% [6][7][8][9][10][11][12]. In order to improve corrosion resistance in super critical pressurized water (SCPW), high-Cr-ODS steels have been developed [7][8][9][10][11][12][13]. However irradiation embrittlement caused by the Fe-Cr phase decomposition under neutron irradiation is a critical issue for high-Cr steels.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the corrosion resistance in high-temperature water diminishes significantly with decreasing chromium concentration below 13% [6][7][8][9][10][11][12]. In order to improve corrosion resistance in super critical pressurized water (SCPW), high-Cr-ODS steels have been developed [7][8][9][10][11][12][13]. However irradiation embrittlement caused by the Fe-Cr phase decomposition under neutron irradiation is a critical issue for high-Cr steels.…”
Section: Introductionmentioning
confidence: 99%
“…As for the effects of the other alloying elements than Cr, it was also shown that an addition of Al is effective to reduce the weight gain of the ODS steels and the effect becomes significant with decreasing Cr content from 19 to 15 wt.% [47,48]. The estimated corrosion layer thickness as a function of temperature and Al contents is shown in Fig.…”
Section: Corrosion In Supercritical Pressurized Watermentioning
confidence: 91%
“…The previous research on the chemical analysis and XRD measurements of the corrosion layer revealed that the layer of Al-free 15Cr-ODS steels consists of three parts, Fe 2 O 3 outer layer, Fe 3 O 4 middle one and (Fe, Cr) 3 O 4 inner one, after the test for 300 h at 510 • C in SCPW dissolved with 8 ppm oxygen [49]. In the Al-added ODS steels, a thin alumina layer was formed at the most inner region of the multi-corrosion layers [47][48][49]. Fig.…”
Section: Corrosion In Supercritical Pressurized Watermentioning
confidence: 99%
“…The ODS steels developed for SFR fuel cladding material contain 12% chromium at most. It is well known that the corrosion resistance in high-temperature water reduces significantly with decreasing chromium concentration below 13% [6][7][8][9][10][11][12]. Thus, the most critical issue for the application of ODS steels to the watercooling solid breeder fusion blanket is to improve their corrosion resistance in super critical pressurized water (SCPW) environment.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work [7][8][9][10][11][12][13], it was reported that the addition of chromium (>13 wt%) and aluminum (4.5 wt%) to the ODS steels were very effective in suppressing the corrosion in a SCPW (783 K, 25 MPa) environment. Addition of aluminum also improves the Charpy impact property of the high Cr ODS steels.…”
Section: Introductionmentioning
confidence: 99%